PENERAPAN SISTEM PERADILAN PIDANA ANAK DALAM KAITAN DENGAN HAK-HAK ASASI ANAK ( STUDI DI PENGADILAN NEGERI KISARAN) - Fahrul Rizal (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
The Juvenile Criminal Justice System is the entire process of Settlement of Child Cases in conflict with the law, starting from the investigation stage to the mentoring stage after the child undergoes the criminal law process. Implementation of Criminal Sanctions for Actions Against Children According to Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, is an "emergency door" for children when the child commits a criminal act on the condition that the child is 14 (fourteen years old) or more and is suspected of committing a crime. a criminal offense punishable by imprisonment of 7 (seven) years or more, and the terms of detention must be stated explicitly in a detention order as regulated in articles 32 (2) and (3) according to the law mentioned above. As long as the child does not commit a crime as regulated in Article 32 (2) and (3), the settlement of a child criminal case must be resolved by means of a. Restorative Justice, namely the settlement of criminal cases by involving the perpetrator, victim, family of the perpetrator/victim and other related parties to jointly seek a fair solution by emphasizing restoration back to its original state, and not retaliation, or by means of b. Diversion namely the transfer of the settlement of children's cases from the criminal justice process to the process outside the criminal justice system as regulated in Chapter I Article 1 paragraph (6) and (7). This is intended to provide special protection for children by providing the best for the interests of children, which is an implementation of children's human rights. And in an effort to provide the best protection for children as well as to equalize the vision and perception between institutions that are competent in upholding children's rights, namely the Courts, Prosecutors, Police and Correctional Institutions, the Government issued Presidential Regulation Number 175 of 2014 concerning Integrated Education and Training for Law Enforcement and Related Parties Regarding the Juvenile Criminal Justice System.